1953
DOI: 10.1136/bmj.1.4813.767
|View full text |Cite
|
Sign up to set email alerts
|

Succinylmonocholine

Abstract: CONGENITAL OBSTRUCTION OF INTESTINE hBnrr 767 MmWICAI Jouiu-x. strongly advocated (Rickham, 1952). Most paediatricians will agree that certain congenital abnormalities such as oesophageal atresias and genito-urinary malformations require the specialized surgical techniques available only at regional contres. Abdominal malformations of the alimentary tract, particularly obstructions of the small intestine, are probably the most urgent of the remedial congenital malformations. Early diagnosis and immediate pre-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…On the other hand, the function of plasma cholinesterase is still the cause of some debate and, although there are several hypotheses, none has been universally accepted. In 1953, Lehman & Silk [6] suggested that plasma cholinesterase prevented inhibition of acetylcholinesterase by removal of choline esters formed during metabolism thus indicating that plasma cholinesterase acts as a protector. Bergman & Wurzel [7] postulated a rôle in the transmission of slow nerve impulses.…”
Section: Physiology Of the Cholinesterasesmentioning
confidence: 99%
“…On the other hand, the function of plasma cholinesterase is still the cause of some debate and, although there are several hypotheses, none has been universally accepted. In 1953, Lehman & Silk [6] suggested that plasma cholinesterase prevented inhibition of acetylcholinesterase by removal of choline esters formed during metabolism thus indicating that plasma cholinesterase acts as a protector. Bergman & Wurzel [7] postulated a rôle in the transmission of slow nerve impulses.…”
Section: Physiology Of the Cholinesterasesmentioning
confidence: 99%
“…In this context, however, it has to be acknowledged that not only the soluble butyrylesterases but also true cholinesterases (e.g., the membrane bound acetylcholinesterases of erythrocytes or lymphocytes) may influence SMC degradation. While the BChE undoubtedly does act faster on SUX than on SMC, true cholinesterases hydrolyze even low concentrations of SMC but do not degrade SUX [11]. Such effects are impossible to grasp using cell free sample matrices (e.g., serum or plasma), and their relevance for the pharmacology of SMC have thus never before been detected or investigated.…”
Section: Effectiveness Of Sample Stabilizationmentioning
confidence: 95%
“…However, in absence of respiratory assistance, a therapeutic dose of SUX may cause a potentially lethal respiratory paralysis [1][2][3]. The drug is degraded within minutes [4][5][6][7][8][9][10] by unspecific cholinesterases (butyrylesterase; EC 3.1.1.8), yielding succinylmonocholine (SMC) as the first, and succinate and choline as subsequent degradation products [11][12][13]. Its fast degradation to eventually endogenous compounds as well as the fact that both SUX and SMC are analytically challenging compounds led to SUX having the reputation of an undetectable poison.…”
Section: Introductionmentioning
confidence: 99%
“…Possible candidates for such polymorphism do not primarily include the BChE (large differences in this enzyme's performance would become manifest in prolonged apnea and therefore be easily discernible), but rather less investigated enzymes with no or more subtle effects on SUX anesthesia [e.g., membrane-bound acetylcholinesterases of (red) blood cells] (25). The present work undoubtedly establishes interindividual differences in the pharmacokinetics of SMC and can therefore be seen to basically support Foldes and Norton's position (21).…”
Section: Discussionmentioning
confidence: 99%